ANALISIS KONTRIBUSI PENDAPATAN USAHA TERNAK KAMBING TERHADAP PENDAPATAN USAHATANI KOPI DI DESA ANUGERAH KEMU KECAMATAN PULAU BERINGIN - aprio munandar; munajat munajat (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2023)
This research is an analysis of the contribution contribution of goat livestock business to the income of coffee farmers in Anugerah Kemu Village, Pulau Beringin District. This study aims to analyze the large contribution of goat business income to the income of coffee farmers in the Anugerah Kemu Village, Pulau Beringin District. The research location is in Anugerah Kemu Village, Pulau Beringin District. The research method used in this study was a survey. The type of data used in this study are primary and secondary data. The data processing method used is using the income analysis formula and contribution formula. The results showed that the average coffee farming income in Anugerah Kemu Village, Pulau Beringin District was Rp.26,977,361, - per year. The average income of goats in Anugerah Kemu Village, Pulau Beringin District is Rp.3,790,751 per year and the contribution value of goat livestock business income to coffee farmers in Anugerah Kemu Village, Pulau Beringin District is 12.32% of the total income of coffee farmers.Keyword: Revenue, Contribution,Goat Farming, Coffee Farming